The Effect of Classical Music Therapy on Pain Intensity Pain in Post Appendicectomy Patients in Room Rose II General Hospital Bina Kasih Medan - Arianus Zebua; Herianto Bangun (SEAN Institute, 2021)
Music therapy is the use of music for relaxation to accelerate the healing, improve mental function and create a sense of prosperity, music has a biological effect on human behavior by involving specific brain functions such as memory, learning, motivation, and emotion. Pain is an important sensation for the body. The sensation of vision, hearing, smell, taste, touch and pain is the result of sensory receptor stimuli. Pain management as part of the nurse's care of the patient's response will differ between patients, Appendectomy is the appendix uplifted by an endoscopic procedure or approach, Appendixitis is a bacterial infection. The trigger factor is the lumen blockage caused by fecalite, lymphoid hypertrophy, dry barium, seed or intestinal worms.This research is quasi experiment, which is done to know the influence of classical music therapy to the intensity of pain in post appendectomy patients with 32 respondents, the method of data collection by way of way and direct observation of respondents, The analysis technique used is t-test with 95% confidence level.The results of this study indicate that to determine the effect of classical music therapy on the intensity of pain in patients post apendiktomi very real and close. Before performing music therapy the mean value of 2.59 after music therapy the mean value of 1.44 suggest to health workers especially to nurses At Bina Kasih General Hospital Medan to provide (Penkes) Health education to patients who experience pain post Apendiktomi.